Investigating Indonesian university students attitudes toward ELF-informed materials in business English contexts - Santoso, Wulandari; Hamied, Fuad Abdul; Muslim, Ahmad Bukhori (Universitas Syiah Kuala, 2025)
Despite the growing research demonstrating the changing role of English as a lingua franca (ELF) in todays globalized world, few studies in Indonesia have examined how learners perceive English language teaching (ELT) materials in relation to ELF. Using both quantitative and qualitative approaches, this study investigates learners attitudes toward the current ELT business materials in light of ELF at a private university in Jakarta. A total of 382 respondents filled out online questionnaires, and 10 of them participated in semi-structured group interviews. The descriptive statistics analysis of the quantitative data demonstrated that the participants perceived that the materials incorporated Indonesian English and other non-native varieties of English, 88.4% and 55.2%, respectively. Regarding cultural representations, over 90% of the participants believed that the learning materials raised their awareness of cultural differences between native and non-native English speakers. Additionally, over 70% of the participants believed that the business scenarios in the materials included diverse linguacultural groups. Nevertheless, the thematic analysis of the qualitative results showed learners negative attitudes toward such materials due to their favoritism toward standard English norms and their regard for these as authentic instances of English in business contexts. Despite the limited scope of this study, the findings indicate that the exposure to ELF-informed materials needs to be accompanied by the provision of awareness-raising tasks which utilize the noticing strategy to allow learners to pay attention to different language functions, features, and varieties in authentic spoken and written texts produced within ELF business settings.